Changes of concave and convex rib–vertebral angle, angle difference and angle ratio in patients with right thoracic adolescent idiopathic scoliosis - Canavese, Federico (Springer-Verlag, 2010)
The aim of this study is to describe the radiological changes in rib–vertebral angles (RVAs), rib–vertebral angle differences (RVADs), and rib–vertebral angle ratios (RVARas) in patients with untreated right thoracic adolescent idiopathic scoliosis and to compare with the normal subjects. The concave and convex RVA from T1 to T12, the RVADs and the RVARas were measured on AP digital radiographs of 44 female patients with right convex idiopathic scoliosis and 14 normal females. Patients were divided into three groups: normal subjects (group 1), scoliotic patients with Cobb’s angle equal or <30° (group 2) and scoliotic patients with Cobb’s angle over 30° (group 3). Overall values (mean ± SD) of the RVAs on the concave side were 90.5° ± 17° in group 1, 90.3° ± 15.8° in group 2 and 88.8° ± 15.4° in group 3. On the convex side, values were 90.0° ± 17.3° in group 1, 86.3° ± 13.7° in group 2 and 80.7° ± 14.4° in group 3. Overall values (mean ± SD) of the RVADs at all levels were 0.5° ± 0.7° in group 1, 4.0° ± 4.8° in group 2 and 8.0° ± 4.0° in group 3. The RVARa values (mean ± SD) at all levels was 1.008° ± 0.012° in group 1, 1.041° ± 0.061° in group 2 and 1.102° ± 0.151° in group 3. RVAD and RVARa values in the scoliotic segment were greater in patients with untreated scoliosis over 30° than in patients with an untreated deformity of <30° or normal subjects. A significant effect between groups was observed for the RVA, RVAD and RVARa variables. Measurement of RVA, RVAD and RVARa should not only be performed at and around the apex of a thoracic spinal deformity, but also extended to the whole thoracic spine.